Faunistic analysis of freshwater zooplankton in small rock pools of Maritime Antarctica - Nabokin, M. (Ukrainian Antarctic Journal, 2022)
Small water bodies like the rock pools are used as a model system for evolutionary and environmental studies with a growing interest. The zooplankton in the rock pools is a most interesting and promising research object. Although the first papers on Antarctic rock pools were published early in the XX century, these water bodies have been not investigated in detail and comprehensively. The paper aims to review and systematize the knowledge on the diversity of the freshwater zooplankton of the Maritime Antarctica, South Shetland Islands and South Orkney Islands. These organisms include meso- and macro- zooplankton (0.2—20 mm) living in the water and unable to propel themselves against a current, 69 taxa in total. The most diverse of them are 52 taxa of rotifers with 4 taxa identified to the subspecies, 44 — to species, and 4 — to genus level. Crustaceans include 16 taxa (14 identified to the species, 1 — to genus, and 1 — to order); 9 taxa belong to branchiopods, 3 — to ostracods, and 4 — to copepods. One insect species, Parochlus steinenii, is present in the plankton at the larval stage. Summarizing these results, the rock pools of the fairly well studied South Shetland Islands and South Orkney Islands (41 and 46 taxa, respectively) exhibit diversity of living organisms similar to the comparable waterbodies from other parts of the world, while the rest of the region has a much lower diversity (11 taxa). However, this discrepancy is presumably a research artifact because so far, only a few special studies have been done in the Maritime Antarctica. For example, at the Argentine Islands three identified taxa only (2 crustaceans and 1 rotifer) are known with a number of rotifers awaiting identification.